Programmable controllers: theory and implementation - Bryan, L.A. (1997)
Introduction programmable controllers, Number systems and codes -- Logic concepts -- Processors, the power supply, and programming device -- The memory system and I/O interaction -- The discrete input/output system -- The analog input/output system -- Special function I/O and serial communication interfacing -- PLC programnming -- Programming languajes -- The IEC 1131 standar and programming languaje -- System programming and implementation -- PLC system documentation -- PLC PROCESS APPLICATIONS: Data measurements and traducers -- Process responses and transfer functions -- Process controllers and loop tuning -- ADVANCED PLC TOPICS AND NETWORKS: Artificial intelligence and PLC system -- Fuzzy logic -- Local area networks -- I/O bus networks -- INSTALLATION AND STAR-UP: PLC star-up and maintenance -- System selection guidelines